Estudo de quartzos em catodoluminescência - H. Couto (2010)
The application of cathodoluminescence microscopy to the study of quartz from different sources aims to show the importance of this technique to distinguish different generations of quartz, and to identify geochemical signatures with different origins. This study was applied to quartz of hydrothermal origin associated with gold mineralization, with lead-zinc epithermal mineralization associated with volcano-sedimentary and magmatic rocks. The colours of cathodoluminescence presented by the different quartz are related to its origin, whatever their provenance